Application of the Maximum Sensitivity Principle in the Optimization of Measuring Point Arrangement in Transversely Isotropic Rock Mass Engineering. (11th June 2022) - Li, Yongtao; Zhang, Zhizeng
Abstract : The inverse analysis method based on in situ measurement information provides a new approach to determine the mechanical parameters of rock mass. The accurate on-site monitoring data is the prerequisite and basis for the success of displacement back analysis. To improve the accuracy of requirement parameters, a reasonable layout program should be developed to optimize the layout of the measuring position. In order to study the optimal arrangement of measuring points in anisotropic rock mass, the layout optimization of measuring points around a tunnel in the transversely isotropic rock mass is studied according to the maximum sensitivity criteria. The influence of the spatial location of the measuring points on the measurement of the tunnel deformation is obtained. The results indicate that the measuring point should be arranged close to the extreme point in the direction of the larger principal stress.